The joint effect of democracy and economic freedom on corruption (2020)
Th is work examines the joint eff ect of democracy and economic freedom on corruption. Th e study used a database of 160 countries from 2010 - 2016, containing information for a set of economic, cultural, historical, and institutional variables. Several researches show that the joint eff ect of economic freedom levels and democracy are essential to fi ght corruption. Th erefore, the most eff ective public policies for countries under study are those focused on the fundamental right of human beings to control satisfying outcomes of their jobs, which holistically encompasses the freedom and rights of production, distribution, or consumption of goods and services.